Resolution of ethical conflicts between cultures (Salud, Arte y Cuidado, 2022)
The alternative means of conflict resolution are a set of tools used to prevent, help, and successfully conclude a controversy without the need to resort to judicial litigation. In this sense, it should be noted that the main methods are: Negotiation, mediation, conciliation and arbitration, being, in themselves, efficient techniques that have procedures and mechanisms that allow to resolve, for the most part and with the least possible inconvenience, the differences between the actors involved; In this sense, in business organizations the existence of conflicts is denoted, however, these conflicts must arise in the same way between cultures, this is nothing more than that clash of interests, emotions, ideas, values ​​or actions that are born between two or more people who form human talent, being imperative the use of the best ways to solve such problems. It is the duty of the manager, taking the same as that person capable of managing any space where it is located, must undertake and grasp all the means, principles, values, including ethics for the correct use of ideas and knowledge in order to stand out maintaining interpersonal relationships and the contribution of mediation to effective management. Taking as reference what is presented, this argumentative type essay based on the interpretation of theoretical criteria that will give birth to a new criterion is proposed.
Keywords: management; conflict resolution; organizational culture